2017
DOI: 10.1111/ijac.12706
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensibility of mixed ferrite humidity sensors by subsequent heat treatment

Abstract: The study presents the effects of different calcination temperatures on the size and morphology of mixed Co‐Ni ferrites, and the respective changes in the magnetic and electrical properties, with emphasis on their applicability as humidity sensors. The data suggests that the heat treatment does not significantly change the magnetic properties, but significant variations on the morphology of the nanoparticles, correlated with large changes in the electrical properties of the nanoparticles in terms of electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…), which are materials that include two types of transition metals, have stood out due to their robust catalytic activity as exhibiting significant potential applications in various fields. In particular, a few of them such as ZnFe 2 O 4 [13,14], NiFe 2 O 4 [15,16,17,18,19,20,21,22], CoFe 2 O 4 [23], MnFe 2 O 4 [24], Ni 1-X Co X Fe 2 O 4 [25], and NiCuZn ferrites [26] have been reported to be greatly promising in the electrical properties of gas sensors and humidity sensors. More interesting, NiFe 2 O 4 with various microstructures have been prepared so far to effectively detect acetone [14,15,16,17], ammonia [18], NO 2 [19], n-propanol [20], and triethylamine [21].…”
Section: Introductionmentioning
confidence: 99%
“…), which are materials that include two types of transition metals, have stood out due to their robust catalytic activity as exhibiting significant potential applications in various fields. In particular, a few of them such as ZnFe 2 O 4 [13,14], NiFe 2 O 4 [15,16,17,18,19,20,21,22], CoFe 2 O 4 [23], MnFe 2 O 4 [24], Ni 1-X Co X Fe 2 O 4 [25], and NiCuZn ferrites [26] have been reported to be greatly promising in the electrical properties of gas sensors and humidity sensors. More interesting, NiFe 2 O 4 with various microstructures have been prepared so far to effectively detect acetone [14,15,16,17], ammonia [18], NO 2 [19], n-propanol [20], and triethylamine [21].…”
Section: Introductionmentioning
confidence: 99%
“…3 Similarly, Seki et al reported ferrites as humidity sensitive by gaining precise insight into the electrical and magnetic characteristics of the materials. 4 A mixed Ni-Co ferrite and the effect of applied calcination temperature on the humidity sensing properties were reported by Virlan et al 5 The humidity sensing of so ferrites like mixed Cu-Zn system has also been observed where formulation of highly sensitive ferrites by doping was discussed as an alternative to the conventional metal oxide-based humidity sensors. 6 Muthurani et al reported the humidity sensing properties of Cu-, Co-and mixed Cu-Co ferrites where CuFe 2 O 4 showed better results than others at room temperature.…”
Section: Introductionmentioning
confidence: 90%
“…Complex oxides, such as spinel oxides and especially spinel ferrites (unit formula AB 2 O 4 ) are very promising materials for sensing different gases, even though they have been much more widely applied as magnetic materials. Spinel ferrites have shown sensitivity to a wide variety of gases, such as H 2 O (humidity), CO, ethanol, acetone, VOCs …”
Section: Introductionmentioning
confidence: 99%